Improving Vocational High School Students' Listening Skills Through Wordwall Based Digital Game Based Learning - M. Adrian Amien Anshari; Edi Pujo Basuki; Mujad Didien Afandi; Savira Zaniar (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
This study aimed to investigate the effect of Wordwall-Based Digital Game-Based Learning on students’ listening skills and determine the extent of improvement after the treatment. The study employed a quantitative approach using a quasi-experimental one-group pre-test and post-test design. The participants consisted of 29 tenth-grade students at a vocational high school in Surabaya. Data were collected through listening tests administered before and after the implementation of Wordwall-based learning activities. The instrument was validated by experts and demonstrated high reliability with a Cronbach’s Alpha coefficient of 0.873. The findings revealed that students’ listening achievement improved significantly after the treatment. The average pre-test score was 57.41, while the post-test average increased to 77.07. The Wilcoxon Signed Rank Test showed a significance value of 0.001 (p < 0.05), indicating a statistically significant difference between pre-test and post-test scores. Furthermore, the N-Gain score of 0.4816 was categorized as moderate improvement. These results indicate that Wordwall-Based Digital Game-Based Learning effectively improves students’ listening skills and enhances engagement during listening instruction.